1998
DOI: 10.1046/j.1365-2516.1998.0040s3053.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recombinant von Willebrand factor in a canine model of von Willebrand disease

Abstract: Dutch Kooiker dogs with hereditary von Willebrand disease have undetectable levels of von Willebrand factor (vWF), resulting in spontaneous haemorrhage of mucosal surfaces similar to the clinical picture of von Willebrand disease in humans. We used this canine model of von Willebrand disease to study the in vivo effects of a new recombinant von Willebrand factor (rvWF) preparation that contained all species of vWF multimers compared with a rvWF fraction containing only low molecular weight multimers (LMW-rvWF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The former are especially useful for pre-clinical study of human VWF concentrates. 80, 81 In the mild (type 1) VWD dogs, desmopressin can be used to discharge VWF from Weibel-Palade bodies in the endothelial cells. It has been shown in VWD dogs that IL-11 results in increased VWF message transcription and increased plasma levels of VWF.…”
Section: Von Willebrand Disease Animalsmentioning
confidence: 99%
“…The former are especially useful for pre-clinical study of human VWF concentrates. 80, 81 In the mild (type 1) VWD dogs, desmopressin can be used to discharge VWF from Weibel-Palade bodies in the endothelial cells. It has been shown in VWD dogs that IL-11 results in increased VWF message transcription and increased plasma levels of VWF.…”
Section: Von Willebrand Disease Animalsmentioning
confidence: 99%
“…In dogs, clinical signs of vWD are similar to those in humans (Schwarz et al. ), and include mucosal haemorrhage, prolonged bleeding following surgery and excessive bleeding with tooth eruption (Schwarz et al. ).…”
Section: Introductionmentioning
confidence: 96%
“…Likewise, infusion of human recombinant VWF into human subjects with severe VWD revealed a VWF:Ag half‐life of 21.9 hours, and a substantial stabilization of endogenous FVIII:C, peaking at 24 hours after infusion . In the canine model of severe VWD, infusion of human recombinant VWF resulted in a VWF:Ag half‐life of 21.6 hours in one dog and 22.1 hours in a second dog with sustained increases in endogenous FVIII levels . In our previous study, we showed that FVIII levels in mouse plasma could be restored up to 800 mU/mL when human recombinant VWF was infused into VWF (null) mice either by intravenous or intraperitoneal administration .…”
Section: Discussionmentioning
confidence: 84%